Aegle marmelos: A novel low cost substrate for the synthesis of polyhydroxyalkanoate by Bacillus aerophilus RSL- 7. (March 2019) - Sabapathy, Poorna Chandrika; Devaraj, Sabarinathan; Parthiban, Anburajan; Pugazhendhi, Arivalagan; Kathirvel, Preethi
Abstract: Conventional plastics have created greater environmental concerns over the past few decades and in turn, have motivated researchers to find an interesting substitute for the petroleum based plastics. Polyhydroxyalkanoates could be valuable alternatives to conventional plastics. The current work presents the investigations carried out to produce PHA by Bacillus aerophilus (RSL- 7) isolated from oil contaminated site while utilizing Bael ( Aegle marmelos ) whole fruit hydrolysate as a low cost substrate. The organism was characterized by 16S rRNA sequencing and other biochemical tests. The produced PHA was extracted by solvent extraction method and chemical characterization was done using FT-IR and thermal characteristics were studied using TGA and DSC analyses, respectively. The highest amount of PHA produced was observed to be 2.47 g/L with a cell dry weight of 21.25 g/L at 72 h of incubation with the supplementation of 1% peptone and glucose, respectively to the fruit hydrolysate.